2021
DOI: 10.3390/molecules26195998
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Ephedra fragilis: Extraction Optimization, Chemical Characterization, Antioxidant and AntiGlycation Activities

Abstract: Response surface methodology (RSM) with a Box–Behnken design (BBD) was used to optimize the extraction of bioactive compounds from Ephedra fragilis. The results suggested that extraction with 61.93% ethanol at 44.43 °C for 15.84 h was the best solution for this combination of variables. The crude ethanol extract (CEE) obtained under optimum extraction conditions was sequentially fractionated with solvents of increasing polarity. The content of total phenolic (TP) and total flavonoid (TF) as well as the antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 73 publications
2
11
1
Order By: Relevance
“…Barapatre et al [ 22 ] and Tung et al [ 20 ] also found both high TPC and ABTS radical scavenging activity in the EtOAc fractions of A. nilotica and A. confusa , respectively. In studies where a crude extract was fractionated by solvents of different polarities, it is often found that higher antioxidant activity occurs in the EtOAc fraction than in n -hexane or DCM fractions [ 23 , 24 ], consistent with the findings of this study.…”
Section: Resultssupporting
confidence: 90%
“…Barapatre et al [ 22 ] and Tung et al [ 20 ] also found both high TPC and ABTS radical scavenging activity in the EtOAc fractions of A. nilotica and A. confusa , respectively. In studies where a crude extract was fractionated by solvents of different polarities, it is often found that higher antioxidant activity occurs in the EtOAc fraction than in n -hexane or DCM fractions [ 23 , 24 ], consistent with the findings of this study.…”
Section: Resultssupporting
confidence: 90%
“…Ephedra fragilis is distributed in North Africa and Europe (▶ Fig. 2 d) [54] as well as in Morocco [44,55] and Austria [43]. Finally, Ephedra nebrodensis, which has the lowest distribution, can be found in North Africa [56], Europe (▶ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, nonpolar compounds such as hydrocarbons and terpenes are more soluble in nonpolar solvents such as hexane, while polar compounds such as phenols and flavonoids are more soluble in polar solvents such as methanol, ethanol, or water [ 16 , 17 ]. By sequentially extracting a plant sample with solvents of increasing polarity, it is possible to selectively extract different types of compounds and separate them from each other based on their polarity [ 15 ].…”
Section: Resultsmentioning
confidence: 99%